DISFUNGSI SEKSUAL SEBAGAI ALASAN PERCERAIAN ( STUDI PUTUSAN No.269 / PDT.G /2022 /PA. PAMEKASAN ) - Susantin, Jamiliya; Amin, Masbahul (Qanuni : Journal of Indonesian Islamic Family Law, 2024)
This research analyzes the legal considerations of Pamekasan Religious Court judges in granting divorce due to sexual dysfunction, in terms of Islamic law and positive law. The approach used is normative qualitative with primary data in the form of decision no. 269/Pdt.G/2022/PA.Pamekasan and related regulations, and secondary data from literature and documents. The results of the research show that the divorce suit was granted because of a physical disability that hindered the purpose of marriage. In Islamic law, the wife has the right to demand a fasakh divorce with proof and a suspension period. In positive law, Article 75 of Law no. 7 of 1989 regulates the defendant's medical examination, but its nature is not absolute. The judge based the decision on disputes and quarrels as stated in Article 19 letter (f) PP No. 9 of 1975 because the defendant was not present and the evidence of physical disability was inadequate.